The evaluation of asparagus (Asparagus officinalis L.) root powder as a feed supplement on enhancing growth, immunity, and alleviating acute crowding stress in rainbow trout (Oncorhynchus mykiss) - Mahyar Zare; Ghasem Rashidian; Hung Quang Tran; Thora Lieke; Tatyana Gebauer; Markéta Dvořáková Prokešová; Deepali Rahi Roy; Dalibor Kodrík; Helena Štěrbová; Vlastimil Stejskal (Aquaculture Reports)
In this study, Asparagus (Asparagus officinalis L.) root powder was evaluated as a feed supplement at levels 10 (A10), 20 (A20), 30 g/kg (A30), and control (without supplement) for rainbow trout (Oncorhynchus mykiss) with initial body weight (20.30 ± 0.17 g). Based on our findings, growth performance remained unchanged across all groups (p > 0.05). Red blood cells were found significantly higher in the asparagus-fed groups compared to the control (p < 0.05). Hematocrit and hemoglobin levels were significantly increased in the A30 and A10 groups, respectively (p < 0.05). Serum cholesterol and triglyceride levels were significantly lower in A20 compared to the control (p < 0.05). Lymphoid cell phagocytic activity was significantly higher in control compared to the A10 and A20. However, myeloid cell phagocytic activity in A10 and A20 was significantly higher than control (p < 0.05). Before stress, serum cortisol levels were similar across all groups (p > 0.05); however, the A30 group exhibited the lowest glucose levels (p < 0.05). One hour post-stress, cortisol levels were significantly higher in A10 and A30 (p < 0.05), while glucose levels remained unchanged (p > 0.05). A30 showed the lowest level of cortisol at 24 h post-stress (p < 0.05) despite no significant changes in glucose among all other groups (p > 0.05). In conclusion, asparagus root powder at the tested levels did not improve fish growth, although the positive impacts on hematological parameters, serum biochemistry, immune responses, and post-stress cortisol regulation in rainbow trout merit further investigation.